A Study Of Individual And Organizational Factors On The Usage Of Personal Protective Equipment Among Workers In The Manufacturing Industry - Jeremiah Nathan, James (2024)
This study to determine the individual and organizational factors toward the usage of personal protective equipment (PPE) among workers in the manufacturing industry. The study included 110 manufacturing workers in total. A structured questionnaire was used to gather demographic data, individual and organizational factors, and PPE compliance. The questionnaire was derived from validated tools and included individual benefits, perceived barriers, self-efficacy, social norms, interpersonal support toward PPE, and organizational emphasis. Data was analysed using IBM Statistical Package for Social Sciences (SPSS) Version 27. Descriptive analysis showed high levels of interpersonal support, as well as organizational emphasis and social norms, among workers, suggestive of both workplace and peer influences on PPE compliance. Specifically, education was significantly positively associated with social norms, interpersonal support and organizational factors, while working experience was positively associated with social norms but negatively associated with perceiving benefits and barriers. The study concludes that PPE compliance can be attributed to a combination of individual and organizational factors in the manufacturing industry. Specifically, they show increased adherence among targeted interventions such as counseling programs targeting workers with less than college education, and mentorship programs targeting older or more experienced workers. Organizational safety culture and better access to PPE also emphasis promoting compliance. Therefore, this study stresses the significance of individual and organizational factors importance on safety culture in manufacturing.